The Impact of media coverage of criminal trials on the impartiality of the courts - Mwanza, Betty Mueni (Strathmore University, 2018)
Court impartiality is a fundamental right that is accorded to accused persons. This right is in pursuit of a broader right of fair hearing which is recognized both internationally and nationally. Various factors contribute to the court bias. They include the normal human cognitive processes that limit a man to his observations. Prior exposure to facts of a criminal case may limit one's mind openness to the facts of a case that do not conform to the ones exposed to before. Therefore, the overall purpose of this paper is to illustrate the relationship between media coverage of criminal trials and court bias in making judicial decisions in criminal cases. This is through objectives such as investigate why criminal proceedings attract media attention; investigating how media portrays criminal proceedings; and investigating how the bias arises in courts as an effect of media coverage. There is a direct and indirect relationship that exists between media and judicial decisions. These exist between the media, the public and the judiciary. There is broad literature that has been covered to illustrate the same and judicial opinions in decided cases have also mentioned this relationship that leads to court bias. It is hoped that this study will inform judicial authorities of the need to balance the freedom of expression of the media and the right of an accused person to a fair trial that will not lead to either of the rights being trumped on.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: Media coverage; Criminal trials; Impartiality; Courts